ADOPTION OF SRI PLANTING SYSTEM IN RANDUAGUNG VILLAGE, LUMAJANG REGENCY, EAST-JAVA, INDONESIA - Reza Safitri (Agricultural Socio-Economics Journal, 2017)
SRI (System of Rice Intensification) planting system is technological innovation which emphasizes on soil function as growth media and source of plant nutrition. Introduction process to the SRI technology in Randuagung Village, Lumajang Regency has implemented for 5 years. However, farmers are still unwilling to implement the system. Therefore, it is necessary to know obstacles that caused slow process of that system adoption. This research was qualitative descriptive and conducted on September to October 2016 to the “Tani Khisma Agung” Farmer Group. Sample determination method that used in this research was snowball sampling, thus it was obtained 2 key informants and 18 informants. Data analysis used interactive model data analysis by Miles , Huberman, and Saldana (2014), which is data condensation, data display, and conclusion drawing or verification. The research result showed that there were obstacles that caused slow process of SRI planting system innovation adoption as follow: Labour system, water availability, less real proofs, program continuity, late assistance, plant pest organism, and cost. Besides that, there were other obstacles such as planning process with top-down system and group counseling method that less appropriate to the actual condition.